Price dynamics in the market of hops - MacKinnon, Douglas (Hmeljarski bilten, 2022)
This research measures the correlation between season average prices for hops with hop stocks and hop hectarage. The Hop Equilibrium Ratio, a measure of the supply/demand relationship for U.S. hops, was introduced. Through the Bayesian inference method, the authors used these data to calculate the effect of an incremental change to one metric had on the probability of directional changes of future U.S. season average prices (SAP). Between 2010 and 2020, the dominance of trademarked and patented varieties created unique powers for supply and price management. Research results enable more accurate price forecasting in the hop industry.
Keywords: alfa-kisline; alpha-acids; Bayesian theorem; Bayesov izrek; brewing industry; economies of scale; ekonomija obsega; equilibrium; hop market; pivovarstvo; ravnovesje; trg hmelja